Regulation of CYP450 and drug transporter mediated by gut microbiota under high-altitude hypoxia - Bai, Xue; Yang, Jianxin; Liu, Guiqin; Zhu, Junbo; Wang, Qian; Gu, Wenqi; La, Linli; Li, Xiangyang (Frontiers in Pharmacology, 2022)
Hypoxia, an essential feature of high-altitude environments, has a significant effect on drug metabolism. The hypoxia–gut microbiota–CYP450/drug transporter axis is emerging as a vital factor in drug metabolism. However, the mechanisms through which the gut microbiota mediates the regulation of CYP450/drug transporters under high-altitude hypoxia have not been well defined. In this study, we investigated the mechanisms underlying gut microbial changes in response to hypoxia. We compared 16S ribosomal RNA gene sequences of the gut microbiota from plain and hypoxic rats. As a result, we observed an altered gut microbial diversity and composition in rats under hypoxia. Our findings show that dysregulated gut microbiota changes CYP3A1 and MDR1 expression under high-altitude hypoxic environments. Thus, our study reveals a novel mechanism underlying the functioning of the hypoxia–gut microbiota–CYP450/drug transporter axis.